2015
DOI: 10.1590/1516-3180.20151334t2
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccines for preventing cardiovascular disease

Abstract: BACKGROUND: This is an update of the original review published in 2008. The risk of adverse cardiovascular outcomes is increased with influenza-like infection, and vaccination against influenza may improve cardiovascular outcomes. OBJECTIVES: To assess the potential benefits of influenza vaccination for primary and secondary prevention of cardiovascular disease. METHODS: Search methods: We searched the following electronic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 1 publication
1
28
0
1
Order By: Relevance
“…A Cochrane review of eight randomized controlled trials with a total of 12,029 participants provides evidence that influenza vaccination decreased cardiovascular outcomes, and a case series study that used a within-person method of comparison found that the risk of stroke was increased after respiratory tract infection but was reduced after vaccination against influenza, pneumococcal infection and tetanus. 168,169 On the basis of this evidence, annual vaccination against influenza may affect stroke rates and could be given to individuals who are at moderate to high risk of stroke, as emphasized in recent guidelines.…”
Section: Stroke Risk Factorsmentioning
confidence: 99%
“…A Cochrane review of eight randomized controlled trials with a total of 12,029 participants provides evidence that influenza vaccination decreased cardiovascular outcomes, and a case series study that used a within-person method of comparison found that the risk of stroke was increased after respiratory tract infection but was reduced after vaccination against influenza, pneumococcal infection and tetanus. 168,169 On the basis of this evidence, annual vaccination against influenza may affect stroke rates and could be given to individuals who are at moderate to high risk of stroke, as emphasized in recent guidelines.…”
Section: Stroke Risk Factorsmentioning
confidence: 99%
“…Influenza vaccination is guideline recommended by the American Heart Association and the American College of Cardiology (Class I, level of evidence B recommendation) (34) and "may be considered" according to The European Society of Cardiology (Class IIb, level of evidence C) (35). When all available information on the subject was condensed in a Cochrane review the conclusion was that additional higher-quality evidence is necessary to confirm whether influenza vaccination is effective in preventing cardiovascular disease (18).…”
Section: Discussionmentioning
confidence: 99%
“…The need for such a study was highlighted in a Cochrane review concluding that additional higher-quality evidence is necessary to confirm whether influenza vaccination is effective in preventing cardiovascular disease (18).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, for influenza vaccination there have been a number of studies , and some reviews , including systematic reviews and meta‐analyses investigating its potential efficacy in preventing acute cardiac events. Influenza vaccination has been reported to reduce (i) the development of a new AMI in patients with chronic heart disease ; (ii) the incidence of AMI in the 60 days following vaccination, compared to the baseline period ; and (iii) the frequency of coronary ischaemic events in patients with optimally treated coronary artery disease .…”
Section: Pneumococcal and Influenza Vaccination And The Prevention Ofmentioning
confidence: 99%
“…Whilst the review articles generally indicated benefit of influenza vaccination in reducing the incidence of AMI, one did indicate that vaccination rates still remained low . The authors of a systematic review and meta‐analysis concluded that in patients with CVD, influenza vaccination appeared to reduce composite CVEs compared to placebo, but not individual outcomes such as AMI, and there was not enough evidence to determine whether vaccination was effective in primary prevention . However, the authors also indicated that since most studies had some risk of bias, further higher quality evidence was required to confirm the findings.…”
Section: Pneumococcal and Influenza Vaccination And The Prevention Ofmentioning
confidence: 99%